Improving a method to analyze the requirements for an information system for consistency - Vasiltcova, Nataliya; Panforova, Iryna; Neumyvakina, Olga (Eastern-European Journal of Enterprise Technologies, 2020)
Modern representations of characteristics of functional requirements virtually have no formalized descriptions. That is why the application of the existing methods for the analysis of requirements faces the problems of formal confirmation or refutation of the fact that a functional requirement has an appropriate characteristic. These problems are particularly pronounced in the analysis of functional requirements for consistency. To eliminate these problems, the task was set to develop formalized descriptions of the situations of the complete and partial inconsistency of knowledge-oriented descriptions of functional requirements and based on the resulting descriptions, to improve the existing method for analysis of functional requirements for consistency of created or modified information system. The knowledge-oriented frame-based description was used as a formal description of the analyzed functional requirement for an information system. In the course of solving this problem, the formalized descriptions of the situations of complete contradiction and partial inconsistency of descriptions of the frames of analyzed functional requirements were developed. It was shown that the situation of complete contradiction is a particular case of a situation of the partial inconsistency of descriptions of analyzed frames. This result was the basis for the improved method for analysis of separate frames of descriptions of functional requirements for consistency. The improved method makes it possible not only to identify situations of complete contradiction and partial inconsistency of analyzed frames but also to quantify the degree of the identified inconsistency. The initial and the improved methods were tested during the analysis of the functional requirements of the problem of planning the individual activity of the academic and teaching staff of a higher education institution. Three typical situations that may arise from the analysis of functional requirements for consistency were considered. It was shown that the improved method makes it possible to find more errors in the descriptions of functional requirements